Current nosological status, pathomechanism and treatment of catatonia - Magdalena Julia Jabłońska; Katarzyna Lipa; Patryk Kaczor; Kamil Leis; Krystian Kałużny; Przemysław Gałązka (Kazimierz Wielki University, 2018)
Catatonia, otherwise known as catatonic syndrome is a frequent neuropsychiatric syndrome characterized mainly by motor disorders. There are many somatic and psychiatric dysfunctions, and the multitude of symptoms included in it make a problem in diagnosis. Moreover, until now the mechanism of pathophysiology of catatonia has not been recognized. Among the hypotheses proposed, one may find theories concerning dysregulation of neurotransmission within the dopamineergic D2 or GABA-A-ergic receptors. For years, catatonia was closely related to schizophrenia, but with the publication of the 5th edition of the Diagnostic and Statistical Manual of Psychiatric Disorders - DSM-5, these disorders were separated, creating the hope that catatonia would be considered as a separate disease entity in the future. Pharmacotherapy involves the use of benzodiazepines in the first line, which are effective in most patients. An alternative is N-methyl-D-aspartic acid (NMDA) antagonists and atypical antipsychotic drugs, the use of which is controversial due to the high risk of neuroleptic malignant syndrome, which is a direct threat to life. In the case of catatonia resistant to benzodiazepines, electroconvulsive therapy (ECT) is effective. At the same time, in order to increase the effectiveness of treatment, electroconvulsive therapy and benzodiazepines are used in parallel, which brings satisfactory results.